Models of shareholder democracy: A transnational approach. Issue 3 (15th November 2018) - SINGER, ABRAHAM; RON, AMIT
Abstract: Existing discussions about shareholder control work with a state-centric and Westphalian conception of democracy. Therefore, they see the corporation as a state-analogue: shareholders (citizens) elect a board (legislature) charged with the responsibility to ensure that the executive follows their 'collective interest'. We claim that state-centric models of democracy are not apt for an environment of corporate governance characterised by complex interdependence, porous boundaries, and criss-crossing relations of weak allegiances. Instead, we suggest that recent theories of transnational democracy provide us with better models for thinking about 'popular' control in such an environment. We look at shareholder democracy not as a system where a single body representing a 'demos' tries to control a single executive; instead, we view shareholders as constituting multiple dêmoi which must coordinate and collaborate to control multiple corporate executives. We emphasise deliberation and communicative power as a central mechanism for these dêmoi of shareholders to effectuate control.